FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP CASH HOLDING PERUSAHAAN - Calvin Willie; Herlin Tundjung Setijaningsih (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study is to examine the effect of liquidity, firm size, leverage, insitutional ownership and profitability on cash holding. This study uses secondary data which was testedusing eviews program 11.0. Samples that have been selected by purposive sampling method and selected as many as 74 manufacture companies as a sample from 198 companies that go public listed on the IDX for the period 2017 - 2019. The results of the research on profitability have significantly positive, and the other variables (institutional ownership, liquidity, leverage andfirm size) are not significant to the cash holding.